Pengaruh Variasi Putaran Dan Bentuk Mata Pisau Pengurai Pada Mesin Pengurai Sabut Kelapa Terhadap Kapasitas Mesin - Cahyono, Fajar Tri; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The utilization of coconut fiber waste at this time is very potential, because the coconut fiber waste a lot of selling value. The coconut processing itself produces 2 kinds of products that are coconut fiber and coconut coir. To increase the effectiveness and capacity of coconut fiber decomposers, it is necessary to perform several variables and in this research will use variation of rotation and shape of coconut fiber decomposition blade. which later expected to produce optimal decomposition. The data retrieval process in this research is by decomposing coconut husk where coconut husk is inserted into the machine weighing 500 gram continuously and observation of the decomposition results and calculate the decomposition time, so as to get the results of the machine capacity. Variations of parsing knife rotation and variation of blade shape of blade on coco fiber decomposition machine influence on the decomposition of coconut coir. In this study the optimal result is at 1420 rpm rotation, time of 47 seconds, for the coconut coir that has been done soaking for 2 hours. The optimal production capacity was at 1420 rpm of the knife rotation and capacity result was 0.0104 gram/ s.Keywords: Coconut fiber extraction machine, Coconut husk, Shape of knife blades.